Real-time counting of wheezing events from lung sounds using deep learning algorithms: Implications for disease prediction and early intervention - Im, Sunghoon; Kim, Taewi; Min, Choongki; Kang, Sanghun; Roh, Yeonwook; Kim, Changhwan; Kim, Minho; Hyun Kim, Seung; Shim, Kyung Min; Koh, Je Sung; Han, Seungyong; Lee, Jae Wang; et al. (PLoS ONE, 2023)
This pioneering study aims to revolutionize self-symptom management and telemedicinebased remote monitoring through the development of a real-time wheeze counting algorithm. Leveraging a novel approach that includes the detailed labeling of one breathing cycle into three types: break, normal, and wheeze, this study not only identifies abnormal sounds within each breath but also captures comprehensive data on their location, duration, and relationships within entire respiratory cycles, including atypical patterns. This innovative strategy is based on a combination of a one-dimensional convolutional neural network (1DCNN) and a long short-term memory (LSTM) network model, enabling real-time analysis of respiratory sounds. Notably, it stands out for its capacity to handle continuous data, distinguishing it from conventional lung sound classification algorithms. The study utilizes a substantial dataset consisting of 535 respiration cycles from diverse sources, including the Child Sim Lung Sound Simulator, the EMTprep Open-Source Database, Clinical Patient Records, and the ICBHI 2017 Challenge Database. Achieving a classification accuracy of 90%, the exceptional result metrics encompass the identification of each breath cycle and simultaneous detection of the abnormal sound, enabling the real-time wheeze counting of all respirations. This innovative wheeze counter holds the promise of revolutionizing research on predicting lung diseases based on long-term breathing patterns and offers applicability in clinical and non-clinical settings for on-the-go detection and remote intervention of exacerbated respiratory symptoms.
Keywords: Algorithms; Child; Deep Learning; Humans; Lung Diseases; Neural Networks, Computer; Respiratory Sounds